Enhancing carbon sequestration in soil with coal combustion products: a technology for minimising carbon footprints in coal-power generation and agriculture - Yunusa, I.; Blair, G.; Zerihun, Ayalsew; Yang, S.; Wilson, S.; Young, I. (Springer Netherlands, 2015)
Coal-fired power generation and agriculture account for more than half of global greenhouse gas emissions, but the coal fly ash (CFA) produced in the former can be a resource for reducing emissions from agriculture to minimise environmental footprints in both industries. Our aim in this study was to test how acidic and alkaline CFA addition could minimise loss of C and N from acidic soil, with or without added manure. We determined composition and structural characteristics of acidic and alkaline CFA for their capacity to adsorb organic carbon, but observed poor adsorption because of low concentrations of cenospheres and unburnt carbon as the primary absorbents in the ash. Addition of CFA had no impact on the loss of carbon or nitrogen from unmanured soil in which concentrations of these nutrients were low. Loss of carbon from manured soil was reduced by 36% with alkaline ashes and by 3-fold with acidic ashes; while loss of N was 30–50% lower with acidic ashes, but 28% higher with alkaline ashes, compared with no ash treatment. The increases in C sparing with CFA addition were achieved not by direct C absorption but by restraining microbial population and respiration, and potentially emissions. Alkaline CFA increased soil pH and if used to substitute just 10% of lime for ameliorating soil acidity would reduce CO2 emission associated with the mining of the lime and its eventual dissolution in soil by ~ 2.66 Tg or 2.8% of Australia’s annual agricultural emissions. High concentrations of oxides of phosphorus, silicon, titanium and clay particles in acidic ashes, and oxides of cations in alkaline ashes, were associated with potential for promoting C storage and acidity amelioration in soil.